Feasibility of Using Gluconolactone, Trehalose and Hydroxy-Propyl Gamma Cyclodextrin to Enhance Bendroflumethiazide Dissolution Using Lyophilisation and Physical Mixing Techniques - Saleh, Ashraf (Pharmaceutics, 2018)
Purpose: Hydrophobic drugs are facing a major challenge in dissolution rate enhancement and solubility in aqueous solutions; therefore, a variety of methods have been used to improve dissolution rate and/or solubility of bendroflumethiazide as a model hydrophobic drug. Methods: In this study, two main methods (physical mixing and lyophilisation) were used with gluconolactone, hydroxyl propyl γ-ccyclodextrin, and trehalose to explore this challenge. Bendroflumethiazide, practically insoluble in water, was mixed with one of the three excipients gluconolactone, hydroxyl propyl γ-cyclodextrin, and trehalose in three different ratios 1:1, 1:2, 1:5. To the best of our knowledge, the dissolution of the drug has not been previously enhanced by using either these methods or any of the used excipients. Samples containing drug and each of the excipients were characterized via dissolution testing, Fourier Transform infra-red spectroscopy, differential scanning calorimetry, and scanning electron microscopy. Results: The used methods showed a significant enhancement in dug dissolution rate; physical mixing significantly, p < 0.05, increased the percentage of the drug released with time; for example, bendroflumethiazide dissolution in distilled water was improved from less than 20% to 99.79% within 90 min for physically mixed drug-cyclodextrin 1:5. The lyophilisation process was enhanced and the drug dissolution rate and the highest drug dissolution was achieved for (drug-gluconolactone 1:1) with 98.98% drug release within 90 min. Conclusions: the physical mixing and freeze drying processes significantly increased the percentage of drug release with time.